Organizational and Economic Aspects of the State Support of the Enterprises and Organizations of National Defense Industry - Y. V. Mishin (Модернизация, инновация, развитие, 2019)
Purpose: the purpose of the work is to prepare reasonable proposals for the development of state support for investment activities – programs of diversification of enterprises and organizations of the defense industry. The relevance of the topic of this article is because the current state support mechanisms do not effectively stimulate the implementation of projects to diversify enterprises and defense industry organizations. Therefore, it is necessary to develop special regulatory documents that take into account the specific features of the organization of production and production of defense-industrial complex (first of all, the “State program for diversification of enterprises and defense-industrial complex organizations”) for a rather long period of time.Methods: the methodological basis of the work is the dialectical method of scientific knowledge, as well as systemic and institutional approaches. In the course of the study, the procedures and instruments of state support for investment activities of business entities used methods of analysis and synthesis, comparison and analogies. The methodological basis of this article was legal documents in the field of investment promotion (Decrees of the President of the Russian Federation, Decrees of the Government of the Russian Federation, orders of ministries, etc.).Results: the article formulates proposals on the methods and procedures of justifying calculations, as well as the procedure and conditions for the provision of target funds. The proposals were developed on the basis of the analysis of the specific features of the organization of production and military products manufactured by the defense industry, as well as existing legal documents in the field of state support for investment activities.Conclusions and Relevance: аt the present stage of development of the Russian economy, the state must not only provide support to enterprises and organizations of the defense industrial complex in the form of concessional loans, subsidize interest rates on them, but also finance research and development costs from the federal budget. It should create interest among potential buyers in their acquisition of civilian products not only by economic, but also by administrative methods. At the same time, projects should be evaluated according to three criteria: the level of competitiveness of products in the world markets, commercial (financial) and budgetary efficiency.